Locking in overseas buyers amid geopolitical conflicts - FAN, Di (Institutional Knowledge at Singapore Management University, 2024)
Geopolitical conflicts, particularly economic ones, introduce significant uncertainties into the global supply chain. The impact of these conflicts on cross-border buyer-supplier transactions remains underexplored, as does the capability of global suppliers to mitigate such risks by locking in their foreign buyers. Employing a combined perspective of resource dependence theory and transaction cost economics, we examine a natural experiment to investigate the effects of the 2018 U.S.-China trade war on the transactional relationships between Chinese suppliers and their U.S. buyers. Our study reveals that the trade war generally adversely affected these buyer-supplier transactional relationships, leading to a negative abnormal transaction value in the affected dyads, which amounted to 18.42% of their pre-event level. However, we find that this adverse impact can be attenuated when Chinese suppliers demonstrate superior innovation capabilities, higher corporate social responsibility performance, or fewer local political ties. These findings yield insights for international suppliers and buyers on strategies to maintain buyer-supplier transactions and minimize the detrimental effects on global supply chain relationships during geopolitical conflicts.